Milk Products Containing Bioactive Tripeptides Have an Antihypertensive Effect in Double Transgenic Rats (dTGR) Harbouring Human Renin and Human Angiotensinogen Genes - Tiina Jauhiainen; Taru Pilvi; Zhong Jian Cheng; Hannu Kautiainen; Dominik N. Müller; Heikki Vapaatalo; Riitta Korpela; Eero Mervaala (Journal of Nutrition and Metabolism)
Tripeptides isoleucyl-prolyl-proline (IPP) and valyl-prolyl-proline (VPP) act as ACE inhibitors in vitro. Double transgenic rats (dTGR) harbouring human renin and human angiotensinogen genes develop malignant hypertension due to increased angiotensin II formation. The present study was aimed to evaluate possible antihypertensive effect of IPP and VPP in this severe model. Four-week-old dTGR were randomized in three groups to receive: (1) water (control), (2) fermented milk containing IPP and VPP, and (3) IPP and VPP dissolved in water for three weeks. Fermented milk, but not peptides in water, attenuated the development of hypertension in dTGR by 19 mmHg versus the control group (P=.023). In vitro vascular function tests showed that high concentrations of the peptides evinced ACE inhibitory properties. In other hypertension related variables, no significant differences between the treatment groups were found. In conclusion, fermented milk product containing IPP and VPP prevents development of malignant hypertension in an animal model.